Renal Complications Related to Checkpoint Inhibitors: Diagnostic and Therapeutic Strategies - Julie Belliere; Julien Mazieres; Nicolas Meyer; Leila Chebane; Fabien Despas (Diagnostics, 2021)
Immune checkpoint inhibitors (ICI) targeting CTLA-4 and the PD-1/PD-L1 axis have unprecedentedly improved global prognosis in several types of cancers. However, they are associated with the occurrence of immune-related adverse events. Despite their low incidence, renal complications can interfere with the oncologic strategy. The breaking of peripheral tolerance and the emergence of auto- or drug-reactive T-cells are the main pathophysiological hypotheses to explain renal complications after ICI exposure. ICIs can induce a large spectrum of renal symptoms with variable severity (from isolated electrolyte disorders to dialysis-dependent acute kidney injury (AKI)) and presentation (acute tubule-interstitial nephritis in >90% of cases and a minority of glomerular diseases). In this review, the current trends in diagnosis and treatment strategies are summarized. The diagnosis of ICI-related renal complications requires special steps to avoid confounding factors, identify known risk factors (lower baseline estimated glomerular filtration rate, proton pump inhibitor use, and combination ICI therapy), and prove ICI causality, even after long-term exposure (weeks to months). A kidney biopsy should be performed as soon as possible. The treatment strategies rely on ICI discontinuation as well as co-medications, corticosteroids for 2 months, and tailored immunosuppressive drugs when renal response is not achieved.